OPTIMALISASI BIAYA PERSEDIAAN BAHAN BAKU BROWNIES MENGGUNAKAN METODE SILVER MEAL DAN MARKOV CHAIN - Wirdatun Nisfi; Elfira Safitri; Rahmadeni Rahmadeni; Ahmad Faizal (Universitas Islam Negeri Imam Bonjol Padang, 2026)
Mona Cake Shop is one of the cake shops in Rumbio Village, Kampar District, Kampar Regency, Riau Province. Mona Cake Shop is often faced with problems that occur, namely insufficient or excess raw material supplies so that the production process does not run well. This study aims to determine the result of optimizing the cost of brownies raw material inventory using the Silver Meal and Markov Chain methods. The method used is this study are the Silver Meal and Markov Chain methods. The Silver Meal method is one method that can solve a problem optimally and simply. The Markov Chain method can future raw material inventory costs. Based on the of the study using two methods, it was obtained that the processing result using the Silver Meal method were much more optimal than the Markov Chain method. Where the cost of raw material inventory in the Silver Meal method id while in the Markov Chain method it is .So it can be seen the most optimal result are using the Silver Meal method.The purpose of this study is to analyze and optimize the inventory costs of brownie raw materials at Mona Cake Shop located in Rumbio Village, Kampar Regency, Riau Province. The problem often faced by the shop is the imbalance in the amount of raw material inventory, namely the occurrence of shortages or excess inventory which causes increased storage costs and disruptions to the production process. This study uses the Silver Meal method to determine the optimal raw material ordering policy and the Markov Chain method to predict inventory conditions in the coming period. The results show that the total cost of raw material inventory using the Silver Meal method is Rp 56,310,388.65 while the Markov Chain method is Rp 107,566,512.71. Based on these results, it can be concluded that the Silver Meal method is more efficient in minimizing raw material inventory costs than the Markov Chain method at Mona Cake Shop